2021
DOI: 10.1037/law0000288
|View full text |Cite
|
Sign up to set email alerts
|

Tele-forensic interviewing to elicit children’s evidence—Benefits, risks, and practical considerations.

Abstract: Tele-forensic interviewing (tele-FI; e.g., via video-conferencing software) may be an effective way of increasing the accessibility of skilled interviewers for children who are questioned as part of a criminal or care and protection investigation. The current COVID-19 pandemic has highlighted how critical it is that we have evidence-based procedures to draw upon when traditional face-to-face interviews cannot be employed. In this paper we discuss the benefits and risks associated with tele-FI, review the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 114 publications
(239 reference statements)
1
21
0
Order By: Relevance
“…Even though past results did not identify consistent patterns of differences across interview modes (see also Brown et al, 2021), four study limitations make it premature to conclude that face-to-face and tele-forensic interviews are equally effective. First, in most studies the children provided testimony shortly after target events, when strong memory traces could have masked condition differences.…”
Section: Testimony From Tele-forensic Interviewsmentioning
confidence: 85%
See 1 more Smart Citation
“…Even though past results did not identify consistent patterns of differences across interview modes (see also Brown et al, 2021), four study limitations make it premature to conclude that face-to-face and tele-forensic interviews are equally effective. First, in most studies the children provided testimony shortly after target events, when strong memory traces could have masked condition differences.…”
Section: Testimony From Tele-forensic Interviewsmentioning
confidence: 85%
“…Although previous studies found minimal differences between face-to-face and tele-forensic interview modes (Brown et al, 2021), the interviewing community expressed concern during the COVID-19 pandemic that screen conversations might make it difficult to build rapport with child witnesses (National Children's Alliance, personal communication, March 20, 2020). The current study, which had a larger sample of young children than earlier reports, replicated previous findings in some ways while also validating interviewers' concerns.…”
Section: Discussionmentioning
confidence: 99%
“… Dickinson et al’s (2021) experimental comparison of face-to-face and tele-forensic interviewing did not find differences between interviewing delivery methods and accuracy of children’s disclosed responses. However, others have highlighted some of the risks (i.e., technology issues, rapport building limitations) as well as benefits of tele-forensic interviewing (i.e., recording of interviews, access to remote locations) ( Brown et al, 2021 ). Moreover, respondents highlighted several concerns regarding the use of tele-forensic interviewing, such as potential security and legal barriers to the admissibility of tele-forensic interviews conducted (i.e., assurances of no coaching by adults in the room).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the current pandemic and other factors (e.g. eyewitnesses living in remote locations, limited space to interview multiple eyewitnesses; Brown et al , 2021), the traditional face-to-face interview might sometimes be difficult to perform soon after the event. Thus, it might be important to use other methods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual interviews could be conducted without requiring the physical presence of the eyewitness, circumventing such problems. However, there are possible limitations that can hinder the use of virtual interviews (Brown et al , 2021). For example, the implementation of social and communicative techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%